El Salvador : Blood on All Our Hands - Thurlow, George, (Social Sciences E-Books Online, Collection 2026., 2026)
On April 29, 1981, journalist George Thurlow was shot by members of the El Salvador Treasury Police on a jungle road in San Salvador. His driver, Gilberto Moran, was killed and Associated Press photographer Joaquin Zuniga was seriously injured. In 2000, Thurlow began a more than two-decade search to find Gilberto Moran's grave and some form of personal redemption. El Salvador: Blood On All Our Hands introduces us to those who fought in the civil war, to U.S. aid workers helping to rebuild the country, as well as everyday Salvadorans who suffered through a war killing 70,000 of their fellow citizens.